Amiodarone-Related Pure Red Cell Aplastic Anemia and Hypothyroidism in a Child With Total Anomalous Pulmonary Venous Connection - Ba, Hongjun; Xu, Lingling; Peng, Huimin; Li, Xuandi; Lin, Yuese; Wang, Huishen; Qin, Youzhen (Frontiers in Pediatrics, 2019)
Introduction: Amiodarone is an effective anti-arrhythmic drug, but there are many clinical side effects that limit its application. There are no case reports of amiodarone-related pure red cell aplastic anemia (PRCA). Case Presentation: Here, we present a case of amiodarone-related PRCA and hypothyroidism in a 7-month-old boy. The patient had a total anomalous pulmonary venous connection (the cardiac type) and had undergone cardiac surgery at the age of 2 months. Eleven days after the operation, atrial tachycardia was observed. Amiodarone was administered orally (15 mg/kg.d), following which the arrhythmia was under control. Subsequently, the patient was prescribed amiodarone (5 mg/kg.d) and discharged. Regular medical consultations were not conducted as required. At 7 months of age (5 months after the operation), the patient returned to the hospital for re-examination. The electrocardiogram showed intermittent sinus bradycardia, occasional junctional escape beats, hemoglobin 7.9 g/DL, and thyroid function—TSH 9.660 uIU/mL. Results: Amiodarone was discontinued. Thyroxine was administered orally. Subsequently, the heart rate improved and TSH returned to normal levels. Nutritional therapy was recommended based on a diagnosis of nutrition-related anemia. A re-visit at 9 months of age showed that the weight was 6 kg, but the routine blood test indicated that hemoglobin was 5.9 g/DL with positive cell anemia and low reticulocyte count. Bone marrow cytology examination suggested PRCA. The hemoglobin level was gradually restored after treatment with prednisone. Conclusion: The use of amiodarone in small infants and young children and its side effects should be carefully monitored. The potential mechanism of amiodarone-related PRCA needs further study.